Self-Powered Dual-Mode Pressure Sensor Based on Porous Triboelectric Nanogenerator for Use in Smart Home System - Yuanzheng Zhang; Ju Chong; Yiqian Mao; Xiangyang Gao; Jinmiao He; Hao Wang; Shishang Guo; Haiwu Zheng (Nanoenergy Advances, 2024)
With the rapid evolution of the Internet of Things (IoT), smart home systems have greatly improved people’s lifestyles and quality of life. However, smart home systems based on a single sensor cannot efficiently control multiple terminals, which limits product penetration into lower-end markets. Here, we have developed a dual-mode smart home system based on a porous triboelectric nanogenerator (TENG), which effectively compensates for the shortcomings of smart home systems being unable to control multiple appliances through a single switch. Benefitting from the remarkable electronegativity of MXene and the ameliorative specific surface area of the friction layer, the output characteristics of the porous TENG are greatly improved. Under the identical external stimulus, the open-circuit voltage (VOC) and short-circuit current (ISC) of the porous TENG were 3.03 and 3.04 times higher than those of the TENG with a pure PVDF membrane used as the friction layer. Thanks to the excellent output performance and good linear relationship between pressure and voltage, the developed dual-mode smart home system could efficiently control multiple terminals through a single sensor. This work not only provides theoretical support for developing high-performance TENGs but also paves the way to designing multifunctional smart home systems.